Implementation Of Mobile Commerce On 3A Jaya Msme Products - Ranti Anggraeni (International Journal of Artificial Intelligence and Robotic Technology (IJAIRTec), 2022)
Mobile Commerce is used as an online sales medium. With Mobile Commerce provides convenience for consumers because information is conveyed faster through their mobile devices with a wider marketing reach. Only by accessing M-Commerce via the internet can you choose the goods you want, know the types of goods available, and can make transactions without being limited by time and distance. Mobile Commerce was built with the aim of increasing sales of 3A Jaya. Therefore, a website was designed to be used as a place for selling snack products. The application is created using PHP and database language using MySQL with XAMP web server. Method system development using Waterfall method. The results of the development of the M-Commerce website application as a medium for online buying and selling transactions and help market and promote 3A Jaya products.